Teachers’ Knowledge Regarding Children’s Health at the Elementary School Level - Sadaf, Naila; Huma, Afshan (Revija za elementarno izobraževanje, 2021)
This article is based on one of the research questions in a larger study that aimed to assess the impact of the school health program at elementary schools in Punjab, Pakistan. It explores whether the school health program was helpful in enhancing teachers’ knowledge regarding major health issues among school children - anaemia, iron deficiency, malnutrition, asthma and breathing problems, and seasonal illness. The study revealed some significant findings, which are discussed with reference to the previous literature; conclusions are reached and recommendations given to improve teachers’ knowledge and skills for improving school health.
Keywords: Teachers’ Knowledge; Health Education; School Health Program